2016
DOI: 10.1002/anie.201601084
|View full text |Cite
|
Sign up to set email alerts
|

An Alkyne Diboration/6π‐Electrocyclization Strategy for the Synthesis of Pyridine Boronic Acid Derivatives

Abstract: Received: ((will be filled in by the editorial staff)) Published online on ((will be filled in by the editorial staff))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…General . Characterization and synthetic procedures for compounds 1 , 2 , 5 , 7 , 8 are reported elsewhere [10b,c] …”
Section: Methodsmentioning
confidence: 99%
“…General . Characterization and synthetic procedures for compounds 1 , 2 , 5 , 7 , 8 are reported elsewhere [10b,c] …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in our lab have demonstrated that aromatic oxime ethers bearing an ortho ‐alkyne group can be transformed into isoquinoline boronic esters via a diboration/6π‐electrocyclization sequence . We therefore began our studies by investigating the applicability of this transformation for the synthesis of borylated thienopyridines as this would deliver a novel class of heteroaromatic boronic ester scaffolds .…”
Section: Methodsmentioning
confidence: 99%
“…Organoboron compounds play an important role in organic chemistry as they can be converted into a wide variety of functional groups [1,2,3,4,5,6,7,8,9,10,11,12,13]. Thus, the synthesis of different types of organoboron compounds continues to be an important research field [14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%